Legacies from nurturers in tourism; inspiring people for communities - Wiltshier, Peter (2017)
In this paper a review of pre-requisites for supply side competency in developing communitybased tourism is offered. Using an interpretive and phenomenological approach, the skills, aptitudes and capacity to nurture within the community, are considered in a focus on improving a destination’s ability to sustain tourism as an element of development. This development agenda is dependent on marshalling an array of skills in a complex, differentiated and individualised marketplace. It is difficult to achieve triple-bottom line sustainability without acknowledging key skills in nurturing planning, policy interpretation, building of networks and partnerships, building relationships with other hosts in the community, understanding and interpreting triple-bottom line sustainability, mentoring others, understanding lifestyle choices, innovating whilst at all times enjoying and living a chosen life (Tinsley and Lynch, 2001). Nine UK based informants prioritise the antecedents of successful tourism development from a community based approach. This paper seeks to identify and illuminate practices amongst stakeholders termed ‘nurturers’ that develop tourism and destinations through excitement of image and identity, engagement of many and often diverse groups of people, capturing values and beliefs that are often inimitable and working with supportive public sector stakeholders.